Assessment of Seasonal and Spatial Surface Marine Water Quality Variation in Semerak River Estuary, Malaysia - Saiful Samsudin, Mohd; Azid, Azman; Iskandar Khalit, Saiful; Milleana Shaharudin, Shazlyn; Lananan, Fathurrahman (International Journal of Engineering and Technology, 2018)
Mangrove estuary is a part of the mangrove ecosystem which plays an important role for the whole ecosystem. Purposely, this study is to assess the spatial and seasonal variation of surface marine water quality in Semerak River estuary. Dissolved oxygen (DO), unionized ammonia (NH3N), total suspended solid (TSS), nitrate (NO3), oil and grease (O&G), phosphate (PO4), faecal coliform (FC), pH, salinity and conductivity are the measured parameters using in-situ and ex-situ technique. Surface marine water samples collected in two monsoon -Southwest Monsoon (July 2016 to September 2016) and Northeast Monsoon (November 2016 to January 2017). The analytical and statistical results indicate that the surface water of the Semerak River estuary that the possible pollution sources coming from major agriculture, fertilizers, fishing boat and sand mining, natural environment from weathering of geologic sources, surface runoff and oil-spill from fishing boat. Marine water samples of future monitoring studies in mangrove estuary will benefit by enabling understanding of pollution loading and coastal water quality. It is essential to plan a workable water quality modelling as powerful tool to simulate marine water quality and forecast future consequences to facilitate mangrove biodiversity conservation. The chemical composition of surface marine water in both season is strongly influenced by anthropogenic inputs.Â Â Â